Peeking beneath the precision floor − II. Probing the chemo-dynamical histories of the potential globular cluster siblings, NGC 288 and NGC 362 - Monty, Stephanie; Yong, David; Massari, Davide; McKenzie, Madeleine; Myeong, GyuChul; Buder, Sven; Karakas, Amanda I; Freeman, Ken C; Marino, Anna F; Belokurov, Vasily; Evans, N Wyn (Monthly notices of the Royal Astronomical Society, 2023)
ABSTRACT The assembly history of the Milky Way (MW) is a rapidly evolving subject, with numerous small accretion events and at least one major merger proposed in the MW’s history. Accreted alongside these dwarf galaxies are globular clusters (GCs), which act as spatially coherent remnants of these past events. Using high precision differential abundance measurements from our recently published study, we investigate the likelihood that the MW clusters NGC 362 and NGC 288 are galactic siblings, accreted as part of the Gaia-Sausage-Enceladus (GSE) merger. To do this, we compare the two GCs at the 0.01 dex level for 20 + elements for the first time. Strong similarities are found, with the two showing chemical similarity on the same order as those seen between the three LMC GCs, NGC 1786, NGC 2210-, and NGC 2257. However, when comparing GC abundances directly to GSE stars, marked differences are observed. NGC 362 shows good agreement with GSE stars in the ratio of Eu to Mg and Si, as well as a clear dominance in the r- compared to the s-process, while NGC 288 exhibits only a slight r-process dominance. When fitting the two GC abundances with a GSE-like galactic chemical evolution model, NGC 362 shows agreement with both the model predictions and GSE abundance ratios (considering Si, Ni, Ba, and Eu) at the same metallicity. This is not the case for NGC 288. We propose that the two are either not galactic siblings, or GSE was chemically inhomogeneous enough to birth two similar, but not identical clusters with distinct chemistry relative to constituent stars.